EFFECT OF ADDING ORGANIC ACID TO DIET IN SOME EGG QUALITY AND INTESTINAL ENVIRONMENT FOR QUAIL - Ghadeer Abd Al menam Mohamed Alrahawi (Mesopotamia Journal of Agriculture)
This study was conducted on quail to investigate the effects of some organic acids on egg qualities characters, enteric ecosystem and reproductive performance. One hundred eightybirds were reared from 1 day to 42 days of age, distributed to 3 treatments, (three replicates, 20 birds / replicate) . 1ST treatment (control) reared on standard ration, 2nd treatment reared on standard ration supplemented with Lactic acid (2.5 mg / kg ration), 3rdtreatment reared on standard ration supplemented with Citric acid (2.5 mg / kg ration). Statistical analysis of data showed that the addition of Organic acid improves significantly (P ≤ 0.05) egg weight, albumen weight, yolk weight, height of albumen, high of yolk, yolk diameter, egg length, shape index, weight of first egg, age oflaying 50% egg laying intensity, weight of male reproductive system and length of oviduct as compared with control treatment . No significantly effects in yolk index, egg width, shell weight, shell thickness and internal shell membranes. Significant decrease in Salmonella and E.Coli. Significant increase in Lactobacillus content and significant increase in Lymphocyte % in male and females quail , in Hetrophils and Esinophils in females treated with Organic acid . Improved H/L ratio in Organic acid treatment as compared with control, andsignificant decreased (P ≤ 0.05) in Coagulation timeand Cholesterol concentration in 2nd and 3rd treatment; In conclusion, organic acids improved the enteric ecosystem , egg quality and reproductive performances .